Evaluating a Hospitalist-Based Intervention to Decrease Unnecessary Antimicrobial Use in Patients With Asymptomatic Bacteriuria. (6th June 2016) - Hartley, Sarah E.; Kuhn, Latoya; Valley, Staci; Washer, Laraine L.; Gandhi, Tejal; Meddings, Jennifer; Robida, Michelle; Sabnis, Salas; Chenoweth, Carol; Malani, Anurag N.; Saint, Sanjay; Flanders, Scott A.
Abstract : OBJECTIVE: Inappropriate treatment of asymptomatic bacteriuria (ASB) in the hospital setting is common. We sought to evaluate the treatment rate of ASB at the 3 hospitals and assess the impact of a hospitalist-focused improvement intervention. DESIGN: Prospective, interventional trial. SETTING: Two community hospitals and a tertiary-care academic center. PATIENTS: Adult patients with a positive urine culture admitted to hospitalist services were included in this study. Exclusions included pregnancy, intensive care unit admission, history of a major urinary procedure, and actively being treated for a urinary tract infection (UTI) at the time of admission or >48 hours prior to urine collection. INTERVENTIONS: An educational intervention using a pocket card was implemented at all sites followed by a pharmacist-based intervention at the academic center. Medical records of the first 50 eligible patients at each site were reviewed at baseline and after each intervention for signs and symptoms of UTI, microbiological results, antimicrobials used, and duration of treatment for positive urine cultures. Diagnosis of ASB was determined through adjudication by 2 hospitalists and 2 infectious diseases physicians. RESULTS: Treatment rates of ASB decreased (23.5%; P =.001) after the educational intervention. Reductions in treatment rates for ASB differed by site and were greatest in patients without classic signs and symptoms of UTI (34.1%; P <.001) or urinary catheters (31.2%; P <.001). The pharmacist-based intervention was most effective at reducing ASB treatment rates in catheterized patients. CONCLUSIONS: A hospitalist-focused educational intervention significantly reduced ASB treatment rates. The impact varied across sites and by patient characteristics, suggesting that a tailored approach may be useful. Infect Control Hosp Epidemiol 2016;37:1044–1051